2014
DOI: 10.2337/dc13-2215
|View full text |Cite
|
Sign up to set email alerts
|

Statins and the Risk of Diabetes: Evidence From a Large Population-Based Cohort Study

Abstract: OBJECTIVETo investigate the relationship between adherence with statin therapy and the risk of developing diabetes. RESEARCH DESIGN AND METHODSThe cohort comprised 115,709 residents of the Italian Lombardy region who were newly treated with statins during 2003 and 2004. Patients were followed from the index prescription until 2010. During this period, patients who began therapy with an antidiabetic agent or were hospitalized for a main diagnosis of type 2 diabetes were identified (outcome). Adherence was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 39 publications
3
73
0
Order By: Relevance
“…Because we did not have data on CV mortality, we could not include the commonly used end point of fatal CV events in our analyses [40]. Furthermore, our study concentrated on the benefits of statin therapy in CV disease prevention; however, those with better adherence to statins may have a greater risk of adverse outcomes such as new-onset diabetes than do those with poor adherence [41]. Finally, healthier individuals are more likely to survive and remain longer in the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Because we did not have data on CV mortality, we could not include the commonly used end point of fatal CV events in our analyses [40]. Furthermore, our study concentrated on the benefits of statin therapy in CV disease prevention; however, those with better adherence to statins may have a greater risk of adverse outcomes such as new-onset diabetes than do those with poor adherence [41]. Finally, healthier individuals are more likely to survive and remain longer in the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…39 They also showed, however, a clear-cut reduction of the risk of coronary events, 37 the protective effect exceeding the diabetes mellitus risk, despite its observed greater size (+32%) than that detected in randomized trials. 40 Indeed, the long-term balance may probably be even more in favor of the beneficial effect of statins than that calculated in the Lombardy HCU database because in RCTs statins have also been shown to reduce the risk of stroke. 41 Furthermore, as mentioned above, patients with a high level of adherence to lipid-lowering treatment also showed a significant reduction in the incidence of dementia, 38 a condition associated with a marked increase in the direct and indirect costs to be covered by health service systems.…”
Section: Safety Concernsmentioning
confidence: 99%
“…For example, risk for new onset diabetes mellitus (NODM) as a result of statin therapy (NNH in Table 1), a clinically important adverse drug reaction (ADR) that has been reported in several analyses [21,22], was significantly associated with statin adherence [23]. In their study, Corrao et al found that patients with high statin adherence (PDC ≥ 75 %) had a significantly higher risk for NODM compared to patients with very low adherence (PDC < 25 %) (adjusted HR 1.32, 95 % CI 1.51-1.66).…”
Section: Revisiting the Risk/benefit Conversation With Nonadherencementioning
confidence: 99%
“…In their study, Corrao et al found that patients with high statin adherence (PDC ≥ 75 %) had a significantly higher risk for NODM compared to patients with very low adherence (PDC < 25 %) (adjusted HR 1.32, 95 % CI 1.51-1.66). Hazard ratios were adjusted for factors that may contribute toward risk for DM (age, sex, choice of statin, concomitant use of other drugs, and history of CVD or other chronic comorbidities) [23]. Body mass index data were not available, but the authors attempted to account for this variable in a sensitivity analysis using Monte Carlo simulation.…”
Section: Revisiting the Risk/benefit Conversation With Nonadherencementioning
confidence: 99%